An embodiment of the cinematographer: emotional and perceptual responses to different camera movement techniques - Yilmaz, Mehmet Burak; Lotman, Elen; Karjus, Andres; Tikka, Pia (Frontiers in Neuroscience, 2023)
We investigate the relationship between camera movement techniques and cognitive responses in audiences, reporting on an experiment exploring the effects of different camera movement methods on viewers' degree of immersion and emotional response. This follows directly from preceding experimental literature and is further motivated by accounts and experiences of practicing cinematographers (authors included), which indicates a correspondence between the two. We designed three different cinematic scenes with indifferent moods, and shot each one time with Steadicam, dolly, handheld, and static camera, resulting in 12 different clips. A total of 44 non-professional participants watched the clips and rated their reactions in terms of arousal and degree of involvement. Experimental results are mixed: movement affects the sense of involvement but not necessarily emotional response. We present and discuss some further explorative results and possible future directions to improve the design. We argue in this contribution that there is value in experimental approaches to cinematography, enabling the systematic study of creative intuitions and audience responses in controlled settings.